Synthesis and characterization of Ni0.5Zn0.4Cu0.1Fe2O4 as a magnetic feeder for electromagnetic transmitter application - Shafie, A. (American Institute of Physics Inc., 2016)
Material ferrites with composition Ni0.5Zn0.4Cu0.1Fe2O4 has been successfully synthesized through sol gel method in difference calcination temperature 600Â°C, 700Â°C, 800Â°C and 900Â°C respectively. The temperatures calcination of the material was obtained from thermo-gravimetric analysis (TGA) results. Phase and crystallite size of material were investigated using X-Ray diffraction (XRD). Microstructure, shape and distribution particles of Ni0.5Zn0.4Cu0.1Fe2O4 were examined using high resolution transmission electron microscopy (HRTEM). Magnetic properties were investigated using vibrating sample magnetometer (VSM). Initial permeability and magnetic loss factor were examined by impedance analyzer. Computer simulation technique (CST) was used to simulate electromagnetic transmitter (antenna) with magnetic feeder. The thermo-gravimetric analysis result shows that the total weight loss of Ni0.5Zn0.4Cu0.1Fe2O4 was completed at temperature 572Â°C. XRD result shows single phase and no secondary phase was detected and it has a variation of crystallite size in the range of 0.2 to 1.3 nm. The HRTEM result exhibits microstructure particle in interval value of 46-89 nm with agglomeration shape. The highest magnetic saturation was founded at highest calcination temperature 900Â°C. The Initial permeability and relative loss factor of the material were 187 and 0.03 respectively. Electromagnetic transmitter with magnetic feeder Ni0.5Zn0.4Cu0.1Fe2O4 exhibits magnitude of magnetic field 1.03Ã10-6 tesla, which is higher as compared to the transmitter without magnetic feeder with magnitude magnetic field 8.4Ã10-14 Tesla. Â© 2016 Author(s).